Flood risk management and shared responsibility: Exploring Canadian public attitudes and expectations. Issue 1 (18th April 2018) - Henstra, Daniel; Thistlethwaite, Jason; Brown, Craig; Scott, Daniel
Abstract : One of the central tenets of the flood risk management (FRM) paradigm is that responsibility for flood mitigation and recovery must be shared with stakeholders other than governments, including property‐owners themselves. However, existing research suggests that this imperative is unlikely to be effective unless property‐owners demonstrate a sense of personal responsibility and are willing to undertake protective behaviours. In Canada, several recent policy changes have effectively transferred more responsibility to homeowners, but it is unclear whether Canadians are ready to accept this obligation. This article presents results from a national survey of Canadians living in high‐risk flood areas, which probed their attitudes concerning the division of responsibility for flood mitigation and recovery among governments, insurers and homeowners, as well as their willingness to adopt protective behaviours. The survey, which received 2, 300 responses from all 10 provinces, indicates that Canadians are willing to accept some responsibility, but for most this perceived responsibility is insufficient to influence their decisions on mitigation and recovery. Governments in Canada could learn from jurisdictions that have addressed this disconnect through policies designed to improve awareness of FRM among property‐owners.